Hvad blev der af den klassiske Kold Krigs-aktivisme? Den nordiske dimension i dansk udenrigspolitik - Olesen, Mikkel Runge; Wivel, Anders (Politik, 2015)
Since the end of the Cold War, Danish foreign policy activism has been characterized by a tightening of the bond to the US and by a gradually increasing Danish willingness to participate in military interventions far from Denmark’s borders. On the surface such activism seems to stand in contrast to the superpower-skeptical Nordic activism of the Cold War era. However, this article argues that Danish activism can be understood as a new variant of Nordic activism, adjusted to a new world order and pursued by di erent means, but still centered on the promotion of classical Nordic values such as social equality and human rights. is Dan- ish approach was not immediately embraced by the other Nordic countries. Recent developments, however, indicate that they are moving closer to the Danish position and that Danish Activism and Nordic activism might be merging once more.